BIM collaboration with data collection tools BIM in automated monitoring and management with corrective privilege - ALSHAWWA, KHALID (My University, 2019)
This thesis aims to drawing a conceptual framework that is believed to hold high potential towards the construction industry in terms of progress, development, saving human efforts, avoiding time lags, increasing the quality and efficiency in delivering construction projects. Another objective of this thesis is to analyze the status the construction industry has nowadays and investigating the main reasons and factors acting as a hindrance for coinciding with the recently developed approaches/technologies in the current era. The drawn conceptual framework is mainly about automating management and monitoring daily activities on construction sites. Automation is labeled in different aspects such as site data collection, automatic modeling of 3D point clouds, automatic compliance checking with pre-assigned parameters, and automatic corrective scheduling. Throughout the analysis of possible hindrances three factors were recognized: human interaction factor, technical shortage factor, and business cycle factor. In conclusion, suggestions are made according to analysis in order to mitigate the significance of these factors. In addition, recommendations for future research are made implicitly within conclusion.
Keywords: BIM and automation; BIM monitoring; Auto-management with BIM; Compliance checking; Automatic corrective scheduling; Slow development